2022
DOI: 10.1155/2022/6022981
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Basal Autophagy, Kangai Injection Enhances Cisplatin Cytotoxicity by Regulating FOXO3a-Dependent Autophagic Cell Death and Apoptosis in Human Lung Adenocarcinoma A549/DDP Cells

Abstract: Cisplatin resistance is one of the major obstacles in the treatment of nonsmall cell lung cancer (NSCLC). Kangai injection (KAI), a Chinese herbal medicine, has been used in tumors as adjuvant treatment, but its exact antitumor mechanism is still unclear. In this study, we first demonstrated that cisplatin-resistant A549/DDP cells showed a higher level of basal autophagy in response to cisplatin treatment with increasing autophagic protein expression levels of Beclin 1, p62, and LC3 compared to cisplatin-sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The main obstacle of platinum-based chemotherapy for advanced NSCLC is chemotherapy resistance. Zhou et al (10) showed higher basal autophagy levels in cisplatin-resistant A549/DDP cells treated with cisplatin, and cisplatin resistance (12). The occurrence and development of tumors are significantly influenced by autophagy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The main obstacle of platinum-based chemotherapy for advanced NSCLC is chemotherapy resistance. Zhou et al (10) showed higher basal autophagy levels in cisplatin-resistant A549/DDP cells treated with cisplatin, and cisplatin resistance (12). The occurrence and development of tumors are significantly influenced by autophagy.…”
Section: Discussionmentioning
confidence: 98%
“…(A) Patients comply with the relevant diagnostic criteria of the NCCN Clinical Practice Guidelines: Non-Small Cell Lung Cancer (2020. V8) (10)…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Apoptosis and autophagy are two distinct mechanisms involved in programmed cell death and regulate important intracellular physiological processes. Studies have shown that herbal components can effectively induce apoptosis and autophagy in the treatment of non-small cell lung cancer [ [10] , [11] , [12] ]. Caspase is a type of cysteine protease, and its activation serves as an important biochemical marker of apoptosis.…”
Section: Discussionmentioning
confidence: 99%